Cinematic Adaptation as a Strategy in Teaching Literature - Stoica, Simona Florentina (Didactica Danubiensis, 2026)
This paper explores cinematic adaptation as a didactic strategy in literature classes, focusing on its potential to support interpretative learning and creative engagement through the use of artificial intelligence – assisted tools. The study addresses the need to adapt literature teaching to the visual and digital profile of contemporary students while preserving the formative value of literary reading. Grounded in theoretical perspectives that regard film adaptation as an autonomous interpretative act rather than a faithful reproduction of the literary text, the research adopts a qualitative case-study approach conducted in secondary education. The teaching experiment involved a comparative analysis of literary texts and their cinematic transposition into short screenplay fragments, supported by artificial intelligence applications for storyboard generation and visual sequencing. The activity indicates increased student engagement, deeper textual understanding, and the development of skills related to interpretation, selection, narrative compression, and creative transposition. Cinematic adaptation functioned as a form of active reading rather than a substitute for literary study, demonstrating that artificial intelligence can support interpretative and creative processes without diminishing the central role of the literary text. The paper proposes a flexible didactic model that integrates digital tools responsibly and offers practical implications for contemporary literature teaching.